E-WOM ON TOURIST DESTINATIONS IN PRIGEN PASURUAN - Sri Suprapti; Mochamad Syaiful Arif; Yurilla Endah Muliatie; Rena Febrita Sarie (SEAN Institute, 2023)
Indonesian tourists have a particular interest in tourist destinations that have unique concepts and are popular among the public. This tourism trend is also supported by current technological sophistication where access to electronic devices and the internet has become part of our daily needs. Word of Mouth (WOM), provides an important role in communicating opinions in the community about a product and exerts influence in shaping consumer attitudes and behavior. With the increasing number of business people and skyrocketing technological developments, alternative destinations and available tourist services will be increasingly diverse. Word of Mouth (WOM) grows and develops into networked communication and spreads from a single one-way communication. With advances in internet technology, it has had an impact on increasing the number of travelers seeking information on tourist destinations and online transactions. The tourist destination in Prigen is one of the tourist destinations in Pasuruan Regency which is famous for its natural and cultural charm. Discussed by many travel circles on various social media and widely published on internet search sites. The formulation of the problem in this study is how tourists use social media and eWOM at tourist destinations in Prigen Pasuruan. The purpose of this study is to find out how tourists use social media and eWOM at tourist destinations in Prigen-Pasuruan. This research is a qualitative research using photo as supporting data